Cystic Fibrosis Lung Disease in the Aging Population - Künzi, Lisa; Easter, Molly; Hirsch, Meghan June; Krick, Stefanie (Frontiers in Pharmacology, 2021)
The demographics of the population with cystic fibrosis (CF) is continuously changing, with nowadays adults outnumbering children and a median predicted survival of over 40 years. This leads to the challenge of treating an aging CF population, while previous research has largely focused on pediatric and adolescent patients. Chronic inflammation is not only a hallmark of CF lung disease, but also of the aging process. However, very little is known about the effects of an accelerated aging pathology in CF lungs. Several chronic lung disease pathologies show signs of chronic inflammation with accelerated aging, also termed “inflammaging”; the most notable being chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrosis (IPF). In these disease entities, accelerated aging has been implicated in the pathogenesis via interference with tissue repair mechanisms, alterations of the immune system leading to impaired defense against pulmonary infections and induction of a chronic pro-inflammatory state. In addition, CF lungs have been shown to exhibit increased expression of senescence markers. Sustained airway inflammation also leads to the degradation and increased turnover of cystic fibrosis transmembrane regulator (CFTR). This further reduces CFTR function and may prevent the novel CFTR modulator therapies from developing their full efficacy. Therefore, novel therapies targeting aging processes in CF lungs could be promising. This review summarizes the current research on CF in an aging population focusing on accelerated aging in the context of chronic airway inflammation and therapy implications.